Dynamic role of personality in explaining COVID-19 vaccine hesitancy and refusal - Baker, Melissa N.; Merkley, Eric (Frontiers in Psychology, 2023)
Vaccine hesitancy and refusal are threats to sufficient response to the COVID-19 pandemic and public health efforts more broadly. We focus on personal characteristics, specifically personality, to explain what types of people are resistant to COVID-19 vaccination and how the influence of these traits changed as circumstances surrounding the COVID-19 pandemic evolved. We use a large survey of over 40,000 Canadians between November 2020 and July 2021 to examine the relationship between personality and vaccine hesitancy and refusal. We find that all five facets of the Big-5 (openness to experience, conscientiousness, extraversion, agreeableness, and emotional stability) are associated with COVID-19 vaccine refusal. Three facets (agreeableness, conscientiousness, and openness) tended to decline in importance as the vaccination rate or COVID-19 cases grew. Two facets (extraversion and emotional stability) maintained or increased in their importance as pandemic circumstances improved. This study highlights the influence of personal characteristics in vaccine hesitancy and refusal and the need for additional work on foundational explanations of these attitudes. It calls for additional research on the dynamics of personal characteristics in explaining vaccine hesitancy and refusal. The influence of personality may not be immutable.